Probing unitary two-time correlations in a neutral atom quantum simulator. (23rd January 2019) - Uhrich, Philipp; Gross, Christian; Kastner, Michael
Abstract: Measuring unitarily-evolved quantum mechanical two-time correlations is challenging in general. In a recent paper Uhrich et al 2017 Phys. Rev. A 96 022127, a considerable simplification of this task has been pointed out to occur in spin-1/2 lattice models, bringing such measurements into reach of state-of-the-art or near-future quantum simulators of such models. Here, we discuss the challenges of an experimental implementation of measurement schemes of two-time correlations in quantum gas microscopes or microtrap arrays. We propose a modified measurement protocol that mitigates these challenges, and we rigorously estimate the accuracy of the protocols by means of Lieb–Robinson bounds. On the basis of these bounds, we identify a parameter regime in which the proposed protocols allow for accurate measurements of the desired two-time correlations.